Performance Analysis of Higher Education in West Java with Value-Driven Business Strategy Model - Pupung Purnamasari; Abdul Latif; Erna Apriani; Fenina Berliana Putri (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
This study aims to determine the role and new findings from the external and internal environment in the value-driven business strategy model on university performance. This type of research is descriptive quantitative research. The research method uses a descriptive quantitative approach, with a purposive sampling technique of 100 respondents who are position holders at universities in West Java. The research data analysis technique uses Structural Equation Modeling - Partial Least Squares (SEM-PLS) with SmartPLS software. The results of the study provide findings on the external environment and the internal environment, which have a significant effect on value-driven business strategy and college performance. Then, the test results related to the indirect relationship of Value-Driven Business Strategy mediate the relationship between the external environment and college performance, and the test results further indicate that the indirect relationship of Value-Driven Business Strategy mediates the relationship between the internal environment and college performance. The implications of the results of the first study on government policies that oversee higher education to improve the performance of higher education, especially with value-based strategies and external environments, such as government internal environments, such as finance in agencies, can be further improved because the results of the study show a significant effect